289. Impact of Clinician Specialty on the Use of Oral Antibiotic Therapy for Definitive Treatment of Uncomplicated Bloodstream Infections. (31st December 2020) - Marcelin, Jasmine R; Keintz, Mackenzie R; Ma, Jihyun; Stohs, Erica J; Alexander, Bryan; Bergman, Scott; Van Schooneveld, Trevor C
Abstract: Background: No established guidelines exist regarding the role of oral antibiotic therapy (OAT) to treat uncomplicated bloodstream infections (uBSIs) and practices may vary depending on clinician specialty and experience. Methods: An IRB-exempt web-based survey was emailed to Nebraska Medicine clinicians caring for hospitalized patients, and widely disseminated using social media. The survey was open access and once disseminated on social media, it was impossible to ascertain the total number of individuals who received the survey. Chi-squared analysis for categorical data was conducted to evaluate the association between responses and demographic groups. Results: Of 275 survey responses, 51% were via social media, and 94% originated in the United States. Two-thirds of respondents were physicians, 16% pharmacists, and infectious diseases clinicians (IDC) represented 71% of respondents. The syndromes where most were comfortable using OAT routinely for uBSI were urinary tract infection (92%), pneumonia (82%), pyelonephritis (82%), and skin/soft tissue infections (69%). IDC were more comfortable routinely using OAT to treat uBSIs associated with vertebral osteomyelitis and prosthetic joint infections than non-infectious diseases clinicians (NIDC), but NIDC were more likely to report comfort with routine use of OAT to treat uBSIs associated with meningitis and skin/soft tissue infections. IDC were more likely to report comfort with routine use of OAT for uBSIs due to Enterobacteriaceae and gram-positive anaerobes, while NIDC were more likely to be comfortable with routinely using OAT to treat uBSIs associated with S. aureus, coagulase-negative staphylococci and gram-positive bacilli. In one clinical vignette of S. aureus uBSI due to debrided abscess, 11% of IDC would be comfortable using OAT vs 28% of NIDC; IDC were more likely to report routinely repeating blood cultures (99% vs 83%, p< 0.05). Figure 1: Clinician comfort using oral antibiotic therapy to treat uncomplicated bacteremia due to specific syndromes Figure 2: Clinician comfort using oral antibiotic therapy to treat uncomplicated bacteremia due to specific organisms Conclusion: Considerable variation in comfort using OAT for uBSIs among IDC vs NIDC exists, highlighting opportunities for IDC to continue to demonstrate their value in clinical practice. Understanding the reasons for variability may be helpful in creating best practice guidelines to standardize decision making. Disclosures: All Authors : No reported disclosures